Red : a crayon's story [book with audioplayer] - Hall, Michael, 1954- ([Library Ideas, LLC], 2017)
A blue crayon mistakenly labeled as "red" suffers an identity crisis in this picture book by the New York Times-bestselling creator of My Heart Is Like a Zoo and It's an Orange